An analysis of the U.S. individual investor sentiment influence on cryptocurrency returns and volatility - SAYIM, MUSTAFA (My University, 2022)
In this research, the U.S. investor sentiment effect on cryptocurrency returns and volatility is examined by separating it into irrational and rational parts. According to the data, an unforeseen rise in the rational part of U.S. individual investor attitude influences cryptocurrency returns statistically and positively. In other words, rational sentiment can result in rising cryptocurrency returns. Additionally, a positive significant association exists between cryptocurrency volatility and the rational part of the individual U.S. investor sentiment. The findings confirm the hypothesis that the behavior of rational investors who utilize and study the impact of economic factors on asset prices reduces cryptocurrency volatility.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; EKONOMİ; Ekonomi ve İş; Sosyal Bilimler (SOC); ECONOMICS; ECONOMICS & BUSINESS; Social Sciences (SOC); Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Cryptocurrency; investor sentiment; VAR model; ASSET PRICES; STOCK; BITCOIN; RISK; INFLATION; EXCHANGE; MARKETS; NEWS; US